Pengaruh Profitabilitas, Leverage, Perusahaan dan Intensitas Modal terhadap Agresivitas Pajak (Studi Empiris Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2017- 2021) - Magdalena Septia Prihana; Titiek Puji Astuti; Agus Endrianto Suseno (Jurnal Pendidikan Tambusai, 2023)
Profitability, leverage, company size, and capital intensity all have an impact on tax aggressiveness, according to an empirical study of property and real estate companies from 2017 to 2021. This study uses secondary data. The research sample consists of eighty real estate and property companies that will be listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. Using a strategy called "purposive sampling," 38 businesses were chosen to serve as samples. Profitability, leverage, firm size, and capital intensity all have a positive impact on tax aggressiveness, according to the study.